The Effect Of Metacognitive Strategy Instruction On Efl Jordanian Undergraduates’ Academic Listening - Adnan Mohammad, Khatatbeh Mohanad (2020)
Listening has been recognised as an essential tool for communication in academic settings. Successful academic listening, in turn, has been found to be correlated with successful use of listening metacognitive strategies. Nevertheless, many Foreign Language (FL) students were reported to command only a limited repertoire of listening metacognitive strategies. Due to this misapprehension, FL students have been reported to 1) gain low scores in their academic listening comprehension performance (ALCP); 2) experience high levels of academic listening anxiety (ALA); and 3) command low levels of metacognitive awareness in academic listening (MAAL). Therefore, this study investigated the viability of metacognitive strategy instruction (MSI) in 1) decreasing students’ ALA; 2) increasing students’ MAAL; and thus 3) enhancing students’ ALCP. Specifically, an MSI intervention programme targeted 34 Jordanian EFL undergraduates, all of whom were female students registered in an intact group of academic listening course at a Jordanian state university.